The Development of Digital Comic as a Learning Media to Enhance Student's Understanding and Awareness on the Topic of Drugs - Haya Taira; Rika Rafikah Agustin; Diana Rochintaniawati (Universitas Pendidikan Indonesia, 2024)
The human mindset significantly affects the progress of Science and Technology. Drugs are one of the examples that result from human complex thought. Lack of understanding of this topic can lead to others experimenting with dangerous psychotropic drugs. Studying sciences using only textbooks will not be imprinted in student memories. Consequently, incorporating media can help the teacher to improve student understanding. This study was aimed to facilitate students' understanding and awareness of the topic of drugs. The ADDIE model is a guideline for developing good media suitable for the topic. The resulting media was judged by an expert, a lecturer, and a teacher, who proceeded to use Index Aiken. The students' responses are gathered using a questionnaire of 20 statements and a Likert scale. The result shows that the lecturer's judgment rater agreement index has a V = 0.9625, indicating a high media score. At the same time, the teacher’s judgment has a V = 0.7875, which indicates an average score for the media. The students' responses show that 56.67% of students strongly agree that the comic can facilitate them to understand and be more aware of drugs. The findings show that lecturers and teachers agree that digital comics have the potential to be educational resources that foster comprehension and awareness and help students learn about drugs.